Heart rate variability status at rest in adult depressed patients: a systematic review and meta-analysis - Wu, Qianqian; Miao, Xiangyang; Cao, Yingying; Chi, Aiping; Xiao, Tao (Frontiers in Public Health, 2023)
Purposes A meta-analysis was conducted to examine the differences in heart rate variability (HRV) between depressed patients and healthy individuals, with the purpose of providing a theoretical basis for the diagnosis of depression and the prevention of cardiovascular diseases. Methods To search China National Knowledge Infrastructure (CNKI), WanFang, VIP, PubMed, Web of Science, Science Direct, and Cochrane Library databases to collect case–control studies on HRV in depressed patients, the retrieval date is from the establishment of the database to December 2022. Effective Public Health Practice Project (EPHPP) scale was used to evaluate literature quality, and Stata14.0 software was used for meta-analysis. Results This study comprised of 43 papers, 22 written in Chinese and 21 in English, that included 2,359 subjects in the depression group and 3,547 in the healthy control group. Meta-analysis results showed that compared with the healthy control group, patients with depression had lower SDNN [Hedges’ g = −0.87, 95% CI (−1.14, −0.60), Z = −6.254, p < 0.01], RMSSD [Hedges’ g = −0.51, 95% CI (−0.69,-0.33), Z = −5.525, p < 0.01], PNN50 [Hedges’ g = −0.43, 95% CI (−0.59, −0.27), Z = −5.245, p < 0.01], LF [Hedges’ g = −0.34, 95% CI (−0.55, − 0.13), Z = −3.104, p < 0.01], and HF [Hedges’ g = −0.51, 95% CI (−0.69, −0.33), Z = −5.669 p < 0.01], and LF/HF [Hedges’ g = −0.05, 95% CI (−0.27, 0.18), Z = −0.410, p = 0.682] showed no significant difference. Conclusion This research revealed that HRV measures of depressed individuals were lower than those of the healthy population, except for LF/HF, suggesting that people with depression may be more at risk of cardiovascular diseases than the healthy population.